Analiza bazy Elsevier - Science Direct pod kątem materiałów wyszukiwanych poprzez słowo kluczowe „bibliotherapy” - Chatzipentidis, Kiriakos (2016)
In the analysis will be examined articles from peer-reviewed scientific journals searched by keyword "bibliotherapy" (bibliotherapy) in Elsevier-Science Direct database.
Keywords: Elsevier-Science Direct; bibliotherapy; bibliotherapy databases; bibliotherapy bibliography; bibliotherapy as a science